Neuroimmune axis: Linking environmental factors to pancreatic β-cell dysfunction in Diabetes - Luz Andreone (Brain, Behavior, & Immunity - Health)
Pancreatic β-cells are specialized in secreting insulin in response to circulating nutrients, mainly glucose.Diabetes is one of the most prevalent endocrine-metabolic diseases characterized by an imbalance in glucose homeostasis, which result mainly from lack of insulin production (type 1 diabetes) or insufficient insulin and peripheral insulin resistance (type 2 diabetes), both influenced by genetic and environmental components. Pancreatic β-cell dysfunction and islet inflammation are common characteristics of both types of the disease. Pancreatic islets are a highly innervated tissue whose function can be influenced by the brain, either directly through the autonomic nervous system or indirectly via neuroendocrine mechanisms. In addition, it is well-established that there is a fine-tuned communication between the immune and neuroendocrine tissues in maintaining endocrine pancreas homeostasis.Various psycho-social, physico-chemical and lifestyle environmental factors have been associated with diabetes risk. In this review, I briefly comment on certain aspects of the psycho-neuro-immune interactions that link environmental factors and the endocrine pancreas, leading to metabolic health or diabetes.Interdisciplinary research, embracing new and broader perspectives, should be conducted to explore strategies for preventing or slowing down the constant increase in diabetes worldwide.